2008
DOI: 10.1590/s1677-55382008000400011
|View full text |Cite
|
Sign up to set email alerts
|

Activity of antioxidant enzymes in seminal plasma and their relationship with lipid peroxidation of spermatozoa

Abstract: Purpose: To determine the activity of seminal plasma catalase (CAT), superoxide dismutase (SOD) and glutathione peroxidase (GPX) and their relationship with malondialdehyde (MDA), as a marker of lipid peroxidation, content of spermatozoa and seminal plasma in normozoospermic and asthenozoospermic males. Materials and Methods: Semen samples were obtained from 15 normozoospermic and 30 asthenozoospermic men. Results: We observed inverse correlations between activities of CAT (k/mL) and SOD (U/mL) in seminal plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
54
2
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 19 publications
11
54
2
4
Order By: Relevance
“…These findings are in accordance with the study of Murawski et al [34]. It must be emphasized that SOD seminal plasma provides protection against lipid peroxidation of phospholipid and phospholipid-bound fatty acids in normozoospermic samples [35,36]. The results of other studies, however, indicate that SOD activity in seminal plasma is lower in men with normozoospermia than in men with pathological spermiogram [37,38].…”
Section: Discussionsupporting
confidence: 91%
“…These findings are in accordance with the study of Murawski et al [34]. It must be emphasized that SOD seminal plasma provides protection against lipid peroxidation of phospholipid and phospholipid-bound fatty acids in normozoospermic samples [35,36]. The results of other studies, however, indicate that SOD activity in seminal plasma is lower in men with normozoospermia than in men with pathological spermiogram [37,38].…”
Section: Discussionsupporting
confidence: 91%
“…Although a number of studies have investigated the relationship between human seminal plasma GPX and semen parameters, results have not been consistent. Lower GPX levels have been reported among infertile men (27,28), as well as in patients with asthenozoospermia (29), while in other studies no relationship between these parameters was detected (30)(31)(32), and, surprisingly, in another study, higher levels of GPX were reported in males with oligozoospermia or asthenozoospermia (33). These discrepancies may be explained by sample sizes.…”
Section: Discussionmentioning
confidence: 92%
“…La actividad de la GPx y la superóxido dismutasa (SOD) provenientes de la fracción conservada de plasma seminal se midieron mediante los kits Ransel ® y Ransod ® (Randox Laboratories, Crumlin, UK), respectivamente, de acuerdo con los procedimientos descritos por Tavilani y colaboradores (25). Para la GPx se preparó una solución de reacción con glutatión (4 mmol/L), NADPH (0,34 mmol/L) y glutatión reductasa (0,5 U/L).…”
Section: Evaluación De La Actividad Antioxidante Enzimáticaunclassified